Analisis Sanitasi Lingkungan Berdasarkan Tempat Pembuangan Sementara (TPS) Sampah pada Rumah Kos Wilayah Kota Semarang - Mutiara Dwi Rahayuni; Vira Aditya Putri; Meirica Dyah Ayu Ambarsari; Widya Arista Faisa; Risma Puji Hastuti (Health Science Udinus, 2023)
Sanitation of public places is one of the efforts that can be made to maintain cleanliness. The minimum requirements for TTU sanitation are solid waste management, dirty water, and human excrement. Based on these sanitation requirements, there are still problems, namely many boarding houses whose garbage containers do not meet the requirements. Open disposal of waste has the potential to pollute the environment and will have a negative impact on public health. The purpose of this research is to analyze the health impacts that will arise as a result of an open waste temporary disposal site. The method in this research is observation by collecting data. Sampling was carried out purposively which was in accordance with the research objectives, namely a sample of five boarding house in the city of Semarang. The observation results show that the boarding house environment has a problem with garbage. This is evident from the observation results which show that there are 4 out of 5 that do not have trash covers and 4 out of 5 boarding houses whose trash cans are breeding grounds for insects. Conclusion: Seeing these results, problems can arise in the surrounding environment and cause disease for residents who live in the boarding house. Therefore, the trash can and lid must be located together in every place. Suggestion: It is better if the owner can provide garbage facilities and trash covers at the boarding house so that the environment is clean, comfortable, and protected from animals that can cause disease.